Foreign Tourists' Perception On the Cultural Value and Attraction of Pacu Jalur Festival - Sri Chairani; Rahmah Fitriani; Amirul Mukminin; Saiful Anwar Matondang; Devi Pratiwy (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2026)
This study explores foreign tourists’ perceptions of the cultural value and attractions of the Pacu Jalur Festival in Kuantan Singingi, Riau, within the context of global visibility generated by digital virality. Addressing a gap in longitudinal visitor analysis, this research employs a mixed-methods approach combining a qualitative case study with descriptive quantitative analysis. Purposive sampling was applied to select international and non local visitors (N=15) attending the August 2025 festival. Data were collected through structured questionnaires and participatory observation. Quantitative data were processed by using descriptive statistics to measure satisfaction levels, while qualitative insights were synthesized through thematic analysis to capture the nuance of on site experiences. Findings indicate that 86% of travel motivations were driven by viral “aura farming” content on social media, underscoring the conversion power of digital platforms. However, on site experiences significantly exceeded expectations, affirming the festival’s intrinsic appeal. Importantly, digital curiosity was transformed into deeper cultural appreciation as tourists developed an understanding of the tradition’s historical and philosophical values through immersive engagement with local communities. While infrastructural challenges such as limited accommodation and language barriers were identified, these were largely mitigated by strong local social capital, particularly community hospitality and informal homestays. In conclusion, Pacu Jalur Festival’s success as a global phenomenon rests on the synergy between digital media as a catalyst and cultural authenticity as the sustaining core. Positive visitor experiences fostered strong repeat visit intentions and effective Word-of-Mouth (WoM) promotion, highlighting the importance of integrating digital promotion with authentic cultural delivery for sustainable tourism growth.